Enhancing Business Performance through Learning Organization and Knowledge Sharing Capability: the Mediating Effect of Innovation Capability using PLS Method - Niko Fanbasten (Bina Nusantara University, 2014)
This research aims to analyze descriptive condition of Learning Organization, Knowledge Sharing Capability, Innovation Capability, and Business Performance perceived by employees at PT SIT GLOBAL SYSTEMS, an IT consultant company. Besides, research is to analyze influence of Learning Organization and Knowledge Sharing Capability (exogenous variables) on Innovation Capability and Business Performance (endogenous variables) in the company. This research used descriptive statistics and associative methods, with primary and secondary data obtained from observation, interview, and questionnaire to 50 employees as respondents. The data then were analyzed with SmartPLS 2.0 software by measuring loading factor (convergent validity), cross loading (discriminant validity), and reliability for outer model, and interpretation of R2 value, path coefficient, and total effect for inner model. Research found that the descriptive condition of Learning Organization and Knowledge Sharing Capability was on average level, whereas the descriptive condition of Innovation Capability and Business Performance was perceived well by the employees. Research concluded that Learning Organization has positive and significant influence on Innovation Capability; Knowledge Sharing Capability has positive and significant influence on Innovation Capability; Innovation Capability has positive and significant influence on Business Performance; Learning Organization has positive and significant influence on Business Performance, directly and indirectly through Innovation Capability; and Knowledge Sharing Capability has positive and significant influence on Business Performance, directly and indirectly through Innovation Capability.